Novel Study of Reaction Kinetics and Mass Transfer in Bioreactor Modelling: Prediction of Bioethanol Fermentation Performance by Saccharomyces cerevisiae on Continuous Fixed Bed Biofilm Plug Flow Reactor - Aslan, Christian; Devianto, Hary; Wonoputri, Vita; Harimawan, Ardiyan (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Bioethanol implementation as a renewable fuel has yielded economic, social, and environmental benefits, including reduced fossil fuel consumption, enhanced energy diversity and supply security, lower greenhouse gas emissions, and support for agricultural communities. These impacts underscore the importance of advancing innovation and optimizing processes to increase bioethanol production. Therefore, basic knowledge of chemical engineering in bioethanol fermentation is important to be learnt as a preliminary study, such as reaction kinetics and transport phenomena. This work studies the reaction kinetics and mass transfer in continuous fixed bed biofilm plug flow reactor modelling to predict anaerobic Saccharomyces cerevisiae fermentation performance, which is still not studied comprehensively. This modelling provides an overview of the influence of various independent variables, namely temperature, initial substrate concentration, cell concentration, superficial flow rate, reactor diameter, and solid particle diameter on various dependent variables, namely final product concentration, residence time, reactor length, reactor volume, product productivity, and pressure drop. The most sensitive parameters related to product productivity are temperature and cell concentration, so in its implementation, the temperature must be controlled at its optimum temperature, and the inoculum must be prepared with high cell concentration. For the next study, it is recommended to study the optimization of reactor design and operation (i.e. the pumping system, cooling system, and pH control of the reactor) and the implementation of the reactor on the plant scale. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).